2017
DOI: 10.1007/s00382-017-3755-1
|View full text |Cite
|
Sign up to set email alerts
|

A new integrated and homogenized global monthly land surface air temperature dataset for the period since 1900

Abstract: A new dataset of integrated and homogenized monthly surface air temperature over global land for the period since 1900 [China Meteorological Administration global Land Surface Air Temperature (CMA-LSAT)] is developed. In total, 14 sources have been collected and integrated into the newly developed dataset, including three global (CRUTEM4, GHCN, and BEST), three regional and eight national sources. Duplicate stations are identified, and those with the higher priority are chosen or spliced. Then, a consistency t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 82 publications
(97 reference statements)
2
69
2
Order By: Relevance
“…We found that over half of the stations showed an increasing trend for EHFs, and change points mainly occurred during 1990s, especially in 1994, a common phenomenon for HWs across the world that was confirmed by many other scholars (Ding et al ., ; Fischer and Schär, ; Wang et al ., ). Meanwhile, we found a dramatic increase of EHFs since the 1990s on a countrywide scale; this phenomenon is consistent with the previous conclusion of the surface air temperature change pattern (Ren et al ., ; Xu et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…We found that over half of the stations showed an increasing trend for EHFs, and change points mainly occurred during 1990s, especially in 1994, a common phenomenon for HWs across the world that was confirmed by many other scholars (Ding et al ., ; Fischer and Schär, ; Wang et al ., ). Meanwhile, we found a dramatic increase of EHFs since the 1990s on a countrywide scale; this phenomenon is consistent with the previous conclusion of the surface air temperature change pattern (Ren et al ., ; Xu et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Several homogenized in situ datasets have been provided for analysis of the interpolation of the surface air temperature data during recent years (Li et al 2010(Li et al , 2017W. Xu et al 2013;Cao et al 2013Cao et al , 2017.…”
Section: A Station Datamentioning
confidence: 99%
“…Here, a temperature station dataset of monthly averages from 1900 to 1990 was used for spatial interpolation. This dataset was constructed by the National Meteorological Information Centre of China, and the temperature records in the dataset have has been quality controlled and homogenized (Li et al 2010(Li et al , 2017W. Xu et al 2013).…”
Section: A Station Datamentioning
confidence: 99%
“…Thus temperature, precipitation, humidity, sunshine, pressure, etcetera, data from ground weather stations continue to be the best source of information for analysing the evolution of the climate over the last 150 years, place the current period in its temporal context, and create databases to evaluate results from the models. This type of data have been compiled by several research centres and resulted in databases covering the world (see the review by Strangeways, 2010), and are well‐known by their acronyms: GHCN (Lawrimore et al ., 2011), GISS (Hansen et al ., 2010), HadCRUTEM4 (Jones et al ., 2012), BEST (Rohde et al ., 2013), which, with some recent contributions (Xu et al ., 2018) are complemented by others created at continental, national and regional scales.…”
Section: Introductionmentioning
confidence: 99%